# Discrete Math

Theorem: For every integer n, if x and y are positive integers with max(x, y) = n, then x = y.
Basic Step: Suppose that n = 1. If max(x, y) = 1 and x and y are positive integers, we have x = 1 and y = 1.
Inductive Step: Let k be a positive integer. Assume that whenever max(x, y) = k and x and y are positive integers, then x = y.
Now let max(x, y) = k + 1, where x and y are positive integers. Then max(x – 1, y – 1) = k, so by the inductive hypothesis, x – 1 = y – 1. It follows that x = y, completing the inductive step.

What's wrong with this proof?

1. 👍
2. 👎
3. 👁
4. ℹ️
5. 🚩
1. max(x,y) has not been previously defined, but I assume it to be:
max(x,y)
=x if x≥y
=y if x<y.

If that is the case, then we can find numerous counter-examples to the given theorem, such as:
x=4, y=6,
n=max(x,y)=6
and x≠y !
which is sufficient proof that the theorem is false.

Notwithstanding the fallacy of the theorem, there are flaws in the proof.

Typically the inductive step is built on the case k and go on to prove that the case k+1 is true.

The assumption part is correctly made:
namely for an integer n=k, and positive integers x and y, if max(x,y)=k, then x=y. (the assumption is correctly made based on the theorem).

So for the case of n=k+1, and max(x,y)=k+1, we only know that at least one of x or y has to be k+1, not both. So there is no logical reason to conclude that both x and y equal k+1. That's where the conclusion that the proof cannot be made.

Could you check that the theorem has been transcribed correctly in the post?

1. 👍
2. 👎
3. ℹ️
4. 🚩
2. Thank you for responding. Yes everything is typed correctly. I want to find what is wrong with proof.

1. 👍
2. 👎
3. ℹ️
4. 🚩
3. Are you convinced that the counter example is valid? If it is, then there is no correct proof, since the theorem is not valid.

If the counter example is not valid, explain why it is not valid.

1. 👍
2. 👎
3. ℹ️
4. 🚩
4. Are you sure the question is not:

"Theorem: For every integer 2n. If x and y are positive integers such that n=x+y and with max(x, y) = n, then x = y."

or did the question say:

"Prove or find a counter example"?

1. 👍
2. 👎
3. ℹ️
4. 🚩
5. No, the question verbatim is "What is wrong with this proof?"

1. 👍
2. 👎
3. ℹ️
4. 🚩
6. Finally, so "What is wrong with the proof" is part of the question. Sorry that I didn't understand it as such before. It seemed to me it was your proof, and I was explaining to you why you should not even try to prove a conjecture full of holes.

Assuming there was a proof, what's wrong had been stated (at 9:52 pm):

"The assumption part is correctly made:
namely for an integer n=k, and positive integers x and y, if max(x,y)=k, then x=y. (the assumption is correctly made based on the theorem).

So for the case of n=k+1, and max(x,y)=k+1, we only know that at least one of x or y has to be k+1, not both. So there is no logical reason to conclude that both x and y equal k+1. That's where the conclusion that the proof cannot be made. "

In addition, by induction, the proof should have been made for the case n+1, and not n-1.

1. 👍
2. 👎
3. ℹ️
4. 🚩
7. Thank you! So, going back to your counterexample in post 9:52:

x=4, y=6,
n=max(x,y)=6

Why does it =6? Sorry if this seems like a silly question. . .

1. 👍
2. 👎
3. ℹ️
4. 🚩
8. "max(x,y) has not been previously defined, but I assume it to be:
max(x,y)
=x if x≥y
=y if x<y. "

So if the above definition max(x,y) corresponds with your teacher's,

then
x=4, and y=6,
then x<y, therefore max(x,y)=y,
so max(4,6)=y.

1. 👍
2. 👎
3. ℹ️
4. 🚩
9. Oh okay. . .I get it. . .Thank you so much for your help :)

1. 👍
2. 👎
3. ℹ️
4. 🚩
10. Here is the solution: The mistake is in applying the inductive hypothesis to look at max(x −1, y −1) . Notice that we are doing induction on n not on x or y. Even though x and y are positive integers, x −1 and y −1 need not be (one or both could be 0). In fact, that is what happens if we let x = 1 and y = 2 when k = 1.

I have to admit I do not quite understand this explanation. . .

1. 👍
2. 👎
3. ℹ️
4. 🚩
11. The inductive process is
1. to establish for a base case, for example n=1. Then,
2. assuming the hypothesis is true for case n (in general),
3. we have to prove that it follows that it is true for the case n+1.

If we are able to do all that, then the hypothesis is true for all n.

Generally, steps 1 and 2 are easy to establish. It is in step 3 that some algebraic or logical operations are required to establish for the case of "n+1".

In the given erroneous proof, the first two steps were correct, but the third step had something to do with x-1 and y-1, which relates to the case n-1 instead of the case n+1. Worse, neither the case n-1 nor the case n+1 had been mentioned, so step 3 had established nothing.

1. 👍
2. 👎
3. ℹ️
4. 🚩
12. It was proven during the previous lecture that
1+2+3+....+n=[n(n+1)]/2.

Using that result, find the sum of all 3-digit palindromes: a palindrome is a number that can be written as ABA, where 1=<A<=9 and 0<=B<=9. Hint: decompose ABA = 100*A + 10*B + A and use above proven result.

1. 👍
2. 👎
3. ℹ️
4. 🚩

## Similar Questions

1. ### C programming

Question: Write a program that reads integers from the keyboard until the user enters the sentinel value -999. The program should then print the minimum integer read, the maximum integer read and the average of all the integers.

2. ### Math(1 question plz help thanks!=D

if two integers have the same absolute value which of the following is true about the integers? A. they must be the same integer B. they must be the opposite integer*** C. they could be the same or opposite integer (plz help my

3. ### Algebra

The larger of two positive integers is five more than twice the smaller integer. The product of the integers is 52. Find the integers. Must have an algebraic solution.

4. ### algebra 1

Find three positive consecutive integers such that the product of the second integer and the third integer is 72.

1. ### math

1)Find the third iterate x3 of f(x)=x2-4 for an initial value of x0=2 A)-4 B)4 C)12 D)-12 I chose C 2)Use Pascal's triangle to expand:(w-x)5 This ones long so I chose w5-5w4x+10w3x3-10w2x4+5wx4-x5 3)Use the binomial Theorem to

2. ### math

An integer is 5 more than another integer. Three times the bigger integer is 11 more than the square of the smaller integer. find the two integers

3. ### Algebra

The sum of two consecutive even integers is 118. A. Define a variable for the smaller integer. B. What must you add to an even integer to get the next greater even integer? C. Write an expression for the second integer. D. Write

4. ### Integers

The larger of two positive integers is five more than twice the smaller integer. The product of the integers is 52. Find the integers.

1. ### algebra2

Two consecutive positive integers have the property that one integer times twice the other equals 612. What is the sum of these two integers?

2. ### Math

Tell whether the difference between the two integers is always, sometimes, or never positive. 1)Two positive integers. Never 2)Two negative integers. Sometimes. 3)A positive integer and a negative integer. Sometimes. 4)A negative

3. ### Math

Explain how you can determine the sign of the sum of two integers if one integer is positive and the other integer is negative.

4. ### Math

The squares of three positive integers are in arithmetic progression, and the third integer is 12 greater than the first. Find the second integer.